Digital Transformation of the B2B Sector: Marketing Aspect - Vyborov E. S., Makarova O. I. (Interactive science, 2020)
this article discusses importance of digital transformation of the B2B sector while the B2C sector shows high growth rates in using digital technologies, only 30% of B2B companies successfully carry out digital transformation. The article presents ways of digital transformation in the field of marketing, reveals the reasons for increasing the importance of the client's holistic experience and offers for digitalization of the B2B sector. Revealing the content of the client's holistic experience, we highlight successful and problematic areas that should allow B2B companies to reorient from a product-centered to a customer-oriented strategy in order to maintain and strengthen their competitive positions.
Keywords: холистический опыт клиента; инвестиции в цифровой опыт; бионические компании; внутренняя и внешняя согласованность; holistic customer experience; investment in digital experience; bionic companies; internal and external consistency